The Application of Underage Marriage in the Islamic Religious Council Patani Region of Southern Thailand - FA, Jalaluddin; RH, Mustiah; Fitra, Tasnim Rahman; Salaemaeng, MR Ibroheng (Alhurriyah, 2023)
The aim of this research is to know the application of underage marriage that was carried out in the Islamic Religious Council of the Patani Region of Southern Thailand and to find out the views of Islamic law on the application of underage marriage that were determined by the Islamic Religious Council. Southern Thailand, Patani Region The Islamic Religious Council of the Patani Region has regulated an age limit for couples who will marry. Even though the age limit has been regulated, there are still underage marriages that are carried out. In this study, the researchers used a type of empirical juridical research with a sociological approach. The results of this study indicate that the application of underage marriage must be carried out by complying with the rules regulated by the Islamic Religious Council of the Patani Region and the rules issued by the Islamic Religious Council of Thailand in 2018 AD. The application of underage marriage carried out in the Religious Council Islam Patani Territory is a legal marriage, does not violate Islamic laws, and can be done by fulfilling the pillars and conditions according to Islamic law.Tujuan dari penelitian ini adalah untuk mengetahuiÂ  penerapan perkawinan di bawah umur yang dilaksanakan di Majelis Agama Islam Wilayah Patani Thailand Selatan dan untuk mengetahui pandangan hukum Islam terhadap penerapan perkawinan di bawah umur yang di tetapkan oleh Majelis Agama Islam Wilayah Patani Thailand Selatan. Majelis Agama Islam Wilayah Patani telah mengatur batas usia bagi pasangan yang akan melaksanakan perkawinan. meskipun suda diatur batas usia tersebut tetap saja masih ada pernikahan dibawah umur yang terlaksana. Dalam penelitian ini peneliti menggunakan jenis penelitian yuridis empiris dengan pendekatan sosiologis. Hasil penelitian ini menunjukkan bahwa penerapan perkawinan di bawah umur harus dilaksanakan dengan memenuhi aturan-aturan yang di tetapkan oleh Majelis Agama Islam Wilayah Patani dan aturan yang di keluarkan Majelis Agama Islam Thailand tahun 2018 M. Penerapan perkawinan di bawah umur yang di laksanakan di Majelis Agama Islam Wilayah Patani adalah perkawinan yang sah dan tidak melanggarkan hukum-hukum Islam dan bisa di lakukan dengan memenuhi rukun dan syarat menurut hukum Islam.